N-Methacryloyl-4-(piperidin-1-yl)-1,8-naphthalimide - Hanton, Lyall R. (International Union of Crystallography, 2010)
In the title compound, C(21)H(20)N(2)O(3), the naphthalimide unit is almost planar (r.m.s. deviation for the 15 non-H atoms = 0.059 Å). The carboximide N atom and the five C atoms of the 2-methylprop-2-enoyl substituent also lie in a plane (r.m.s. deviation = 0.009 Å), which subtends an angle of 84.34 (7)° to the naphthalamide plane. This orients the =CH(2) group of the vinyl fragment towards the naphthalimide rings, giving the molecule an extended configuration. The piperidine ring adopts a chair conformation and there is evidence for some delocalization between the naphthalene and piperidine units, the C—N(pip) bond length being 1.404 (4) Å. In the crystal structure, π–π contacts with centroid–centroid distances of 3.5351 (18) and 3.7794 (18) Å supported by C—H⋯O hydrogen bonds link adjacent molecules in a head-to-tail fashion, forming dimers. These are further stabilized by other C—H⋯O contacts of varying strength, which stack the molecules down the b axis.